Case Report: Sequential lymphomas: may HLA system play a role in this uncommon phenomenon? - Verrou, Evgenia; Diamanti, Ioanna; Fylaktou, Asimina; Daiou, Aikaterini; Dalampira, Dimitra; Dimitriadou, Xanthippi; Tara, Vassiliki; Karadrakonti, Elissavet; Triantafyllou, Theodora; Sevastoudi, Aggeliki; Vlachaki, Efthimia; Karampatzakis, Nikolaos; et al. (Frontiers in Oncology, 2025)
The sequential occurrence of diffuse large B‐cell lymphoma (DLBCL) in a patient diagnosed with classical Hodgkin lymphoma (cHL) or vice versa represents a rare situation. In parallel, human leukocyte antigen (HLA) has been studied extensively about rising susceptibility in various lymphomas. Herein, we present clinical characteristics, the outcome and the results of HLA class-I and class-II investigation in patients sequentially diagnosed with the above-mentioned combination of lymphomas. We describe 8 patients (6 males/2 females) with median age at diagnosis of first and second lymphomas of 45.5 years (range: 25–74 years) and 57.5 years (range: 30–83 years), respectively. The median interval between the first and the second diagnosis was 6.5 years (range: 4–22 years). Regarding HLA investigation, we observed that four of our patients were HLA‐DQB1*03:01 positive. Interestingly, three of our patients displaying this HLA allele developed a third lymphoma. Notably, we observed that the HLA profile of three other patients revealed the presence of HLA-B*35:03. Interestingly, both above-mentioned HLA alleles have been associated with autoimmune manifestations. Although the presence of certain HLA alleles in our patients could be coincidental, our results suggest that HLA typing may be a field of investigational interest regarding patients with sequential lymphomas.